Integrated smart system for the coordination of traffic light traffic management and intelligent public lighting in Hungary - Nikolett, Fecser; Árvai, Tamás; Hausel, István; Könözsy, László Z.; Lakatos, István (Budapest University of Technology and Economics, 2022)
In our study, the operation of a smart system in current operation and the implementation plan of traffic management by traffic lights of a junction are presented. Public lighting has a major effect on the efficacy of cities and the well-being and safety of their inhabitants. The energy consumed for public lighting entails significant costs for the urban management. In our constantly evolving world, there is an ever-growing demand for lighting, leading to the increase in expenses, as well. Smart cities are dedicated to apply the most energy-efficient solution in order to decrease expenses in respect of the safety of all road users.
Keywords: junction; traffic management; motion sensor; smart city; HDMR system; public lighting